Susceptibilidad a deslizamientos de la vía de integración barrial, tramo urna de la Virgen-barrio Panamá, ciudad de Loja, cantón Loja, provincia de Loja. - Guamán Ramos, Diego Fabián (2016)
This thesis aims to identify and characterize landslide prone areas in the route of neighborhood integration (Km 6), in the section from Urna de la Virgen - Barrio Panama, Loja - Ecuador. In this project field and office work were held; applying engineering techniques to obtain data from surveys: topographic, geological, geomorphological, slopes and vegetation cover, the geotechnical characterization addition to direct methods based on SPT (standard penetration test) and indirect VES (Vertical Electrical Sounding); thereof which they serve to correlate water content in the layers and lithology sector. To obtain the final landslide susceptibility maps, heuristic method is used in combination with the rank sum method and the deterministic method; all this with the help of GIS (ArcGIS 10.1) 3.6 Ilwis, interpretation of aerial photographs, digital elevation models, etc. The methodology used by the heuristic method results in maps of the four variables and their weight: Earrings (0.4), Geology (0.3), Geomorphology (0.2), existing land use (0.1); all this procedure is carried out with the "Model Builder" tool. To obtain the susceptibility map by using the deterministic method, calibration parameters were implemented, these were obtained by standard penetration test (SPT) like: soil density, cohesion, heights, angle of internal friction, gravity, water density and thickness of the soil; all this procedure is performed with the help of the " SINMAP " tool. As a result of the main objective, the landslide susceptibility map of the heuristic method in the study area was classified into 5 categories: very low (29.38 %), low (30.60 %), Medium (16.69 %), high (15.63 %) and very high (7.58 %). Furthermore, landslide inventory was made in order to correlate with the susceptibility map, where most of them are highly susceptible zone; each zone is related to the characterization of geomaterials based on mechanical and physical properties of soils SPT. The susceptibility map by the deterministic method has been classified in the same way into 5 categories; higher stability (15.85 %), lower threshold Zone stability (24.85 %), almost stable (21.66 %) Moderately stable (9.91 %) and Stable (27.71 %) threshold area, each area relating to the properties mechanical and physical parameters obtained by studying SPT. The results of this project will allow to zone areas that are susceptible to slip so that there could be a base for the implementation of public policies aimed at preventing risks on the road and its surroundings, as well as being key elements in planning projects and Land Management.